2006
DOI: 10.1051/0004-6361:20053212
|View full text |Cite
|
Sign up to set email alerts
|

The 10 $\boldsymbol{\mu}$m amorphous silicate feature of fractal aggregates and compact particles with complex shapes

Abstract: We model the 10 µm absorption spectra of nonspherical particles composed of amorphous silicate. We consider two classes of particles, compact ones and fractal aggregates composed of homogeneous spheres. For the compact particles we consider Gaussian random spheres with various degrees of non-sphericity. For the fractal aggregates we compute the absorption spectra for various fractal dimensions. The 10 µm spectra are computed for ensembles of these particles in random orientation using the well-known Discrete D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…These spectra are flat and do not show any silicate emission band. We refer to a study of Min et al (2006), where it was found that the silicate band disappears if the averaged dust grain size exceeds ∼4 μm.…”
Section: Radial Gradient Of the Dust Composition In Circumstellar Dismentioning
confidence: 99%
“…These spectra are flat and do not show any silicate emission band. We refer to a study of Min et al (2006), where it was found that the silicate band disappears if the averaged dust grain size exceeds ∼4 μm.…”
Section: Radial Gradient Of the Dust Composition In Circumstellar Dismentioning
confidence: 99%
“…O'Donnell (1994) also did not find any shift in the 10 μm or 18 μm features for the grains containing silicates with the inclusions of carbons (glassy and amorphous). Min et al (2006Min et al ( , 2007 have used DDA to study the composite and aggregated silicates and found that the 10 μm feature shifts to the shorter wavelengths. Jones (1988) found enhancement in the infrared absorption features at 9.7 μm and 18 μm for porous silicate grains and hollow spheres.…”
Section: Introductionmentioning
confidence: 99%
“…The 10 µm silicate feature of aggregates of different fractal dimension was studied in detail by Min et al (2006a). The conclusion of this study is that for the same aggregate mass (so the same r V ) the feature is stronger when the fluffyness of the aggregate is increased (i.e.…”
Section: The Solid State Featuresmentioning
confidence: 77%
“…Fig. 11 (taken from Min et al 2006a) displays this very clearly. The way to understand this is that the particle needs to become 'optically thick' for the feature to decrease in strength.…”
Section: The Solid State Featuresmentioning
confidence: 83%
See 1 more Smart Citation